The National Science Olympiad for English Language Learners at Yogyakarta Elementary Schools: Constraints and Strategies - Azizah, Dinar Martia (JELLT (Journal of English Language and Language Teaching), 2024)
The presence of some National Sains Olympiad questions which are written in English is a challenge not only faced by students but also by teachers who are assigned to train them for the Olympiad. Therefore, the purpose of this study is to describe the constraints faced by the students in doing Mathematics and Science Olympiad tests which are written in English and the strategies implemented by the teachers during the trainings on Olympiad. This research is a case study conducted at five Yogyakarta elementary schools which won National Science Olympiad. This study was conducted by employing interviews with ten students who won the Olympiad in the field of Mathematics and Sciences; and five coaching teachers, observation of training activities, and document studies on training materials. The data was then analyzed by using interactive analysis model namely data condensation, data presentation, and conclusion drawing/verification. The results showed that the constraints faced by students in doing Mathematics and Science in English language, such as the students’ misunderstanding of the meaning of specific terms in Math and Science, the difficulty in understanding sentence stucture of the questions, and the low reading ability of the students. Strategies of the teachers in Olympic training such as simplify the language in the questions, giving assistance during the trainings on Olympiad, collaboration of Mathematics, Science, and English teachers, and the use of technology. The implications of this study were the presence of demands to expand the coverage of English learning materials goal and to improve its teaching quality through integrated learning materials and collaboration with other teachers. Therefore, learning material development and design of teachers’ collaboration in Olympic training can be explored deeper in further research. Keywords: National Science Olympiad, English Language Learners, elementary schools, constraints, strategies